Women Who Study in Madrasah School Experienced Higher Number of Female Circumcision Compared to Western or English Schools - Salmah Lao Manalocon- Basher (Philippine Association of Institutions for Research, Inc., 2016)
Female circumcision refers to the procedures that intentionally alter or cause injury to the female external genital organs. The reasons for doing this vary but it is commonly observed in places where Muslims predominate. The study is intended to determine: 1) the rate of females who had undergone female circumcision in Madrasah School compared to those who went to English schools, 2) the prevalence rate of female circumcision among Meranaos, and 3) the practices and experiences of women who have undergone FC. The study utilized a combination of quantitative and qualitative methods using a designed questionnaire, interview and focus group discussions with the respondents. The results showed that more girls who were studying in Madrasah have undergone this practice compared to the number of girls who are in Western or English schools. It also showed that the prevalence rate of this practice is indeed high in the rural areas, which is 86%. The practice of FC is performed either during Fridays, Holidays or Mondays and Thursdays. Each mentioned day has meanings and there are certain procedures and instructions being followed in doing the practice. In conclusion, religious justification remains the strong reason why FC is still rampantly performed in the different rural areas of Lanao del Sur, Philippines.